Uncertainty and Hyperinflation: European Inflation Dynamics after World War I - Jose A. Lopez; Kris James Mitchener (Center for Economic Studies and ifo Institute (CESifo), 2018)
Fiscal deficits, elevated debt-to-GDP ratios, and high inflation rates suggest hyperinflation could have potentially emerged in many European countries after World War I. We demonstrate that economic policy uncertainty was instrumental in pushing a subset of European countries into hyperinflation shortly after the end of the war. Germany, Austria, Poland, and Hungary (GAPH) suffered from frequent uncertainty shocks – and correspondingly high levels of uncertainty – caused by protracted political negotiations over reparations payments, the apportionment of the Austro-Hungarian debt, and border disputes. In contrast, other European countries exhibited lower levels of measured uncertainty between 1919 and 1925, allowing them more capacity with which to implement credible commitments to their fiscal and monetary policies. Impulse response functions show that increased uncertainty caused a rise in inflation contemporaneously and for a few months afterward in GAPH, but this effect was absent or much more limited for the other European countries in our sample. Our results suggest that elevated economic uncertainty directly affected inflation dynamics and the incidence of hyperinflation during the interwar period.
Keywords: E31; E63; F31; F33; F41; F51; G15; N14; 330; hyperinflation; uncertainty; exchange rates; prices; reparations